Politeness In “La La Land (2016)” Movie: A Pragmatics Study - fachryan raditya maulana (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2024)
This research explores politeness strategies in the film La La Land (2016), employing Brown and Levinson's Politeness Theory as a framework. The study identifies four primary types of politeness strategies: positive politeness, negative politeness, bald on-record, and bald off-record Through qualitative analysis of the film's script, the research aims to uncover the specific politeness strategies utilized by characters, alongside the contextual factors influencing their usage. Key findings indicate that characters employ positive politeness to enhance interpersonal relationships, while negative politeness is used to mitigate potential conflicts. Bald on-record strategies are characterized by directness, reflecting close relationships or urgent contexts, whereas bald off-record strategies rely on indirect communication to navigate sensitive topics. The analysis reveals that intrinsic payoffs, power dynamics, and social distance significantly influence the selection of politeness strategies among characters. This study contributes to understanding how communication styles in cinematic narratives reflect broader social interactions and relationship dynamics.